2023
DOI: 10.3390/jcm12062227
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Preventive Foraminotomy before Laminectomy Combined with Pedicle Screw Fixation May Decrease the Incidence of C5 Palsy in Complex Cervical Spine Surgery in Patients with Severe Myeloradiculopathy

Abstract: C5 palsy is a frequent sequela of cervical decompression surgeries for cervical myeloradiculopathy. Although many researchers have suggested various risk factors, such as cord shifting and the correction of lordotic angles, the tethering of the C5 root beneath the narrow foramen is an independent risk factor for C5 palsy. In this study, we tried to investigate different techniques for foramen decompression with posterior cervical fusion and assess the incidence of C5 palsy with each technique depending on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…This approach can provide additional direct and indirect foraminal decompression through foraminotomy-uncovertebrectomy and foraminal-height increases. Furthermore, the decision-making process in surgery can potentially be influenced by the national healthcare service in the authors' country [4].…”
Section: Surgical Indication and Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…This approach can provide additional direct and indirect foraminal decompression through foraminotomy-uncovertebrectomy and foraminal-height increases. Furthermore, the decision-making process in surgery can potentially be influenced by the national healthcare service in the authors' country [4].…”
Section: Surgical Indication and Techniquementioning
confidence: 99%
“…The combined approach has shown minor complications and better clinical outcomes for multilevel cervical spondylotic myeloradiculopathy and degenerative kyphosis cases [1][2][3]. Techniques and protocols concerning multiple-stage operations for the combined approach have been developed, and it has been confirmed that certain techniques, such as posterior foraminotomy, can reduce complications such as C5 palsy or prevertebral swelling [4,5]. In the combined approach, deciding which way to proceed with posterior fixation is critical.…”
Section: Introductionmentioning
confidence: 99%